2012
DOI: 10.1016/j.jplph.2012.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Organ-dependent oxylipin signature in leaves and roots of salinized tomato plants (Solanum lycopersicum)

Abstract: Oxylipins have been extensively studied in plant defense mechanisms or as signal molecules. Depending on the stress origin (e.g. wounding, insect, pathogen), and also on the plant species or organ, a specific oxylipin signature can be generated. Salt stress is frequently associated with secondary stress such as oxidative damage. Little is known about the damage caused to lipids under salt stress conditions, especially with respect to oxylipins. In order to determine if an organ-specific oxylipin signature coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…These results provide the evidence for the possibility that DkLOX3 or DkLOX3 -derived products play a positive role in abiotic stresses response by modulating the expression of ABA-dependent and other stress-responsive genes. Several studies also found that products of lipid derivatives were suggested to act as secondary messengers to activate some stress-associated genes and activate the response of the plant to desiccation and salinity ( Ingram and Bartels, 1996 ; Shinozaki and Yamaguchi-Shinozaki, 1997 ; Ben-Hayyim et al, 2001 ; Sofo et al, 2004 ; Ghanem et al, 2012 ). In CaLOX1 -OX plants under ABA treatment as well as normal conditions, smaller stomatal aperture was both found and this indicated CaLOX1 or CaLOX1 -derived oxylipins played a role in ABA-independent stomatal closure, nevertheless, with drought and salinity treatments, ABA-induced gene expression in CaLOX1 -OX Arabidopsis was enhanced ( Lim et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results provide the evidence for the possibility that DkLOX3 or DkLOX3 -derived products play a positive role in abiotic stresses response by modulating the expression of ABA-dependent and other stress-responsive genes. Several studies also found that products of lipid derivatives were suggested to act as secondary messengers to activate some stress-associated genes and activate the response of the plant to desiccation and salinity ( Ingram and Bartels, 1996 ; Shinozaki and Yamaguchi-Shinozaki, 1997 ; Ben-Hayyim et al, 2001 ; Sofo et al, 2004 ; Ghanem et al, 2012 ). In CaLOX1 -OX plants under ABA treatment as well as normal conditions, smaller stomatal aperture was both found and this indicated CaLOX1 or CaLOX1 -derived oxylipins played a role in ABA-independent stomatal closure, nevertheless, with drought and salinity treatments, ABA-induced gene expression in CaLOX1 -OX Arabidopsis was enhanced ( Lim et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…PO signatures are influenced by the type of stressor, the plant species being stressed, and the affected organ(s), as well as by the pathogen lifestyle (for reviews see [4,18,[31][32][33][34][35][36][37][38]). For instance, tobacco (Nicotiana tabacum) leaves infected by the hemibiotroph Pseudomonas syringae accumulate high levels of α-dioxygenase (α-DOX) and 9-lipoxygenase (LOX) products [39], whereas certain potato cultivars infected by Phytophthora infestans and tomato leaves infected by necrotrophic Botrytis cinerea accumulate 9(S)-and 13(S)-polyunsaturated fatty acid (FA) (PUFA) hydroperoxides (HPOs) [40][41][42].…”
Section: Shaping the Po Signaturementioning
confidence: 99%
“…Depending on plant species and tissue specificity [47], this pathway produces diverse subsets of alcohols, aldehydes, divinyl ethers, esters, epoxides, hydroxides, hydroperoxides, ketols, ketones and triols [46,48] (Figure 3). These metabolites are implicated in nearly all plant biological processes that include defense, development and trans-kingdom communication [40,49].…”
Section: 13-lipoxygenasesmentioning
confidence: 99%